The Methane Majors: Climate Change and Animal Agriculture in U.S. Courts - Bray, Daina; Poston, Thomas M. (Columbia Journal of Environmental Law, 2024)
Over two dozen lawsuits have been filed in U.S. courts against fossil fuel companies by state and local government plaintiffs alleging cli-mate harms and deceptions. But there are other central actors beyond these “Carbon Majors” that contribute heavily to the warming climate. Prominent among them is the animal agriculture sector, a significant emitter of greenhouse gases overall and an especially important source of potent methane emissions. Animal agriculture has thus far escaped most climate litigants’ notice. In jurisdictions around the world, though, the industry has begun to face serious legal challenges premised on its role in driving climate change. After developing a first-of-its-kind comparative survey highlighting the most consequential legal challenges to date, this Article explores the present reality and future possibilities of climate change and ani-mal agriculture litigation in the United States. With lessons and prec-edents drawn from both foreign and U.S. case law, we chart a variety of strategic courses that those who seek to hold animal agriculture ac-countable might consider. Given the United States’ outsized role in the global animal agriculture industry and inadequate regulation of its climate harms, climate change and animal agriculture litigation—whether successful in court, the court of public opinion, or both—could prove a powerful driver of climate change adaptation and mitigation in the years to come. As this Article demonstrates, a spate of “Methane Majors” cases may be on the horizon.